Slam and navigation of indoor robot based on ROS and lidar - Yang, Xiaozhuo (Journal of physics. Conference series, 2021)
For indoor service robot, this paper designs an indoor robot based on ROS (robot operating system) operating system. The robot uses two-dimensional lidar as the core sensor to collect the depth information of the environment and uses SLAM algorithm based on particle filter to realize the robot mapping; Based on the framework of ROS, A* algorithm and DWA algorithm are used to realize the navigation function of the robot; The map and navigation are simulated in the gazebo simulation environment to verify the function of path planning, local obstacle avoidance and navigation.